Eficiência Hidráulica e Energética da Operação do Bombeamento para o Abastecimento do Bairro de Mangabeira em João Pessoa - Montenegro, Leonardo Leite Brasil (2009)
This study aims to present alternatives to the operational control at the pumping station to supply water to the district of Mangabeira in Joao Pessoa, providing greater energy efficiency and water and thus reducing the cost of electricity. The system consists of two pumping stations that pump water to a conduit head high, making the distribution by gravity. First we carried out a diagnostic of the current configuration of the system, where it was analyzed to meet the demand, the survey of facilities and operating conditions. The modeling of the current situation and the proposed alternatives were performed with the software EPANET 2.00.12, in order to compare the various settings. The results show that it is possible to use only one lift station for the existing demand, requiring only the touch of another pump in parallel during the peak hours of consumption.